Accumulation of soil carbon under elevated CO2 unaffected by warming and drought - Dietzen, Christiana A.; Larsen, Klaus Steenberg; Ambus, Per L.; Michelsen, Anders; Arndal, Marie Frost; Beier, Claus; Reinsch, Sabine; Schmidt, Inger Kappel (Global change biology, 2019)
Elevated atmospheric CO2 concentration and climate change may substantially alter soil carbon (C) dynamics, which in turn may impact future climate through feedback cycles. However, only very few field experiments worldwide have combined elevated CO2 (eCO2) with both warming and changes in precipitation in order to study the potential combined effects of changes in these fundamental drivers of C cycling in ecosystems. We exposed a temperate heath/grassland to eCO2, warming, and drought, in all combinations for 8 years. At the end of the study, soil C stocks were on average 0.927 kg C/m2 higher across all treatment combinations with eCO2 compared to ambient CO2 treatments (equal to an increase of 0.120 ± 0.043 kg C m−2 year−1), and showed no sign of slowed accumulation over time. However, if observed pretreatment differences in soil C are taken into account, the annual rate of increase caused by eCO2 may be as high as 0.177 ± 0.070 kg C m−2 year−1. Furthermore, the response to eCO2 was not affected by simultaneous exposure to warming and drought. The robust increase in soil C under eCO2 observed here, even when combined with other climate change factors, suggests that there is continued and strong potential for enhanced soil carbon sequestration in some ecosystems to mitigate increasing atmospheric CO2 concentrations under future climate conditions. The feedback between land C and climate remains one of the largest sources of uncertainty in future climate projections, yet experimental data under simulated future climate, and especially including combined changes, are still scarce. Globally coordinated and distributed experiments with long‐term measurements of changes in soil C in response to the three major climate change‐related global changes, eCO2, warming, and changes in precipitation patterns, are, therefore, urgently needed. Exposure of a temperate heath/grassland to elevated CO2 (eCO2), warming, and drought, in all combinations for 8 years resulted in a progressive increase in soil carbon stocks under eCO2. The response to eCO2 was not affected by simultaneous exposure to warming and drought. The robust increase in soil C under eCO2 suggests that there is continued and strong potential for enhanced soil carbon sequestration in some ecosystems to mitigate increasing atmospheric CO2 concentrations under future climate conditions